ANÁLISIS SEMIÓTICO DEL SEÑOR DE LA JUSTICIA EN LA IDENTIDAD CULTURAL DE LOS RIOBAMBEÑOS EN EL PERIODO JULIO – DICIEMBRE 2017 - Unach (2019)
The research entitled “Semiotic analysis of the Lord of Justice in the cultural identity of the riobambeños in the period July – December 2017”. This research has the objective to strengthen the cultural identity of the inhabitants of Riobamba. The theoretical framework is structured with themes and sub-themes related to the dependent and independent variable. The research methodology, part of the illustration of the methods, type and design of the research, population and sample established with 397 inhabitants to be surveyed, techniques and instruments used for data collection, which it was supported by practical instruments that is the survey and interview, for which we have prepared a survey and interview guide, by the analysis and discussion of results will allow us to determine the conclusions and recommendations. As a result, it could be mentioned, that this research is intended to be of great impact in virtue of the obtain results, which allows us to observe part of the cultural identity in the riobambeños in the same way an essential part in its daily transcend and how it has been affected with the change of era giving opening to new millennial generations.